The importance of staying within range: associations between tacrolimus intrapatient variability and kidney transplant outcomes - Benning, Louise; Wittig, Lisa; Reineke, Marvin; Busse, Maarten; Speer, Claudius; Zeier, Martin; Morath, Christian; Tran, Thuong Hien; Döhler, Bernd (Frontiers in Immunology, 2026)
BackgroundKidney transplantation remains the treatment of choice for end-stage kidney disease. Maintaining immunosuppression within the appropriate therapeutic range is essential to prevent rejection and ensure long-term graft survival. This study evaluated the clinical relevance of different tacrolimus exposure metrics and their association with post-transplant outcomes in a real-world kidney transplant cohort.MethodsOf 881 adult deceased-donor kidney transplants performed between 2011 and 2020 at Heidelberg University Hospital, 372 recipients with a functioning graft at day 180 met the inclusion criteria and were included in the final analysis. Tacrolimus trough levels between days 90 and 180 were used to calculate different exposure metrics, including intrapatient variability (IPV), maximum quotient, minimum trough levels, and the area under the curve (AUC) to approximate time spent below the therapeutic threshold. Outcomes analyzed included 5-year death-censored graft survival, 5-year overall graft and patient survival, 3-year rejection-free survival, and 3-year donor-specific antibody (DSA)-free survival.ResultsHigh tacrolimus IPV (≥30%) was associated with a 2.4-fold increased risk of rejection (95% CI 1.3–4.6; P=0.009). A high quotient (≥3.0) was linked to a 2.3-fold higher risk of rejection (95% CI 1.2–4.5; P=0.014) and showed a trend toward worse graft survival (HR 1.9; 95% CI 1.0–3.6; P=0.050). Prolonged time below target levels (<6 ng/mL; AUC ≥0.2) was significantly associated with increased risks of graft failure (HR 3.4; 95% CI 1.9–6.0; P<0.001), death-censored graft failure (HR 4.0; 95% CI 2.1–7.6; P<0.001), and patient death (HR 4.1; 95% CI 1.6–10.3; P=0.003). Minimum trough levels <5 ng/mL were also strongly associated with adverse outcomes, including graft failure (HR 3.2; 95% CI 1.8–5.7; P<0.001), death-censored graft failure (HR 4.0; 95% CI 2.1–7.8; P<0.001), patient death (HR 3.4; 95% CI 1.3–9.0; P=0.012), and rejection (HR 2.5; 95% CI 1.3–4.6; P=0.005). No association was observed between any of the exposure metrics and the development of DSAs.ConclusionsMultiple markers of tacrolimus underexposure were independently associated with poor post-transplant outcomes. These findings underscore the critical importance of maintaining tacrolimus levels within the target therapeutic range during the early post-transplant period to optimize long-term kidney transplant outcomes.